The Role of Duolingo Application in Broadening Indonesian EFL Learners’ Vocabulary Knowledge - wijaya, kristian (Fakultas Ilmu Budaya, Universitas Brawijaya, 2024)
To better expand EFL learners’ vocabulary knowledge in second-language classrooms, educators should instill a more profound awareness of the maximization of potential technological platforms to be further internalized in their daily teaching-learning routines. Regarding this fundamental second language learning principle, Duolingo appeared to be one of the beneficial digital learning tools in nurturing EFL learners’ vocabulary knowledge expansion. Previous researchers contended that Duolingo could provoke more positively sound and authentic second language learning dynamics where EFL learners elevated their vocabulary knowledge to the fullest potential. This small-scale library study employed a thematic analysis method in analyzing the previously generated studies derived from 20 Duolingo and vocabulary scientific articles. A thematic analysis approach was applied to yield more well-organized, apprehensible, and relatable research results contributable to the entire second language vocabulary learning dynamics development. From the obtained research findings, two main themes were proffered: (1) Duolingo application promoted greater vocabulary learning enjoyment and (2) EFL learners gained more significant vocabulary knowledge improvements through Duolingo application.